DAMPAK PENGELUARAN PEMERINTAH TERHADAP PERTUMBUHAN EKONOMI: STUDI KASUS PANEL DATA - Nur Widiastuti; Samsubar Saleh (Center for Economic Studies Universitas Katolik Parahyangan, 2019)
ABSTRACTThe relationship between government expenditures and economic growth is an ambiguous relationship. The results of previous empirical studies indicate that the relationship between the two variables can be a positive or negative relationship. The purpose of this study is to investigate a more detailed relationship between economic growth and government expenditures. The detailed information between these two variables is obtained by investigating the direction of the relations in three levels, i.e. in various countries, in Indonesia, and in provinces in Indonesia. Furthermore, this research also investigates the variables which can drive the economic growth in those three groups of estimations. This research is conducted by using fixed effects panel data method for 96 countries and 33 provinces in Indonesia. The countries’ data are estimated for the period of 1991–2014, while the provinces in Indonesia data are estimated for the period 2011–2013. Based on the results, it can be concluded that the relationship between government expenditures and economic growth depends on many factors. Moreover, the results also show variations in the relations between the two observed variables in the three groups of estimations.Keywords: economic growth; government expenditures; panel data; fixed effects model